BUDAYA HUKUM DAN IMPLIKASINYA TERHADAP PEMBANGUNAN HUKUM NASIONAL - Sesse, Muh. Sudirman (DIKTUM: Jurnal Syariah dan Hukum, 2013)
The culture of law is acceptance and resistance on a law event indicating each human behavior on legal problem and event brought in to community. The law cant be only seen from the yuridical perspective, but it must be seen by several perspective according to people and nation development either developed or developing countries. National development is an absolute requirement to improve people life, nation, and state.